Evolution of Institutes and Mechanisms of Spatial Development of the Economy - Prus, Yuliia (Social Economics, 2019)
This article summarizes the arguments and counterarguments within the scientific discussion on issues of evolution of institutes and mechanisms of spatial development of the economy as the main factor in ensuring the competitiveness of the territory in the conditions of the newest trends of networking, intellectualization and digitalization of social and economic processes. The relevance of solving this scientific problem is that due to an ineffective spatial organization Ukraine loses 2-3 % of GDP annually; the World Bank Report declares to take into account the spatial factor in economic development; territorial socio-economic integration and spatial development are chosen as one of the key goals of the State Strategy for Regional Development for the period up to 2020. The systematization of literary sources and approaches on the subject of research has shown that each country includes a variety of regions, each of which has a specific ecosystem of science and innovation, a unique economic context and industrial infrastructure. Under such conditions, a key tool in ensuring balanced spatial development, in particular to determine the territory of the localization of the growth poles, is smart specialization strategy. The research examines the issues of changing the paradigm of implementing regional policy on the basis of specialization from the period of the operation of the council of national economy to the creation of clusters at the current stage of development of the Ukrainian economy. As the globalization of productions, communities and knowledge networks, increasing the number of network communications leads to the fact that a high level of cooperation becomes one of the key conditions of the country’s competitiveness, the research examines the evolution of cooperative models for key stakeholders (from single helix to quintuple helix) and spatial development institutes. Prospects for further research in this area are the development of recommendations on the coordination of the interests of key stakeholders of the cooperative models in order to ensure the harmonious economic development of Ukrainian territories.